(untitled) (CIPEEX, 2025)
Self-medication is a common practice among medical students, often influenced by advances in academic periods and increased pharmacological knowledge. This study aims to identify aspects related to the influence of academic progress on self-medication for the relief of gastrointestinal symptoms in medical students. A systematic review of the literature was conducted using databases such as PubMed, Scielo, and BVS, covering articles published between 2018 and 2023. The results suggest that students in more advanced stages are more likely to practice self-medication due to the confidence gained from pharmacological knowledge and direct contact with patients. A greater tendency toward self-medication was found among students in the more advanced semesters of the medical course. However, due to the scarcity of studies in the literature on the subject, the finding cannot be considered definitive.